Professor Dr. Yatimah Alias appointed as 6th UMPSA Vice-Chancellor - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 13 January 2025 – Professor Dr Yatimah Alias, 55, has been appointed as the Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) for two years, effective 13 January 2025.